Application and evaluation of variable frequency energy-saving technology for reciprocating compressor in CBM Field. Issue 4 (February 2019) - Wang, Jingyue
Abstract: Reciprocating compressor is the most important gas transportation equipment and the most important energy consumption equipment in the CBM gathering and transportation system. The existing variable clearance volume energy saving adjustment method of reciprocating compressor has the characteristics of complex operation and poor timeliness in operation. By carrying out risk identification, developing test scheme and determining control parameters, we successfully completed power frequency high speed reciprocating compressor variable frequency test. The theoretical analysis and practical operation results show that the application of high voltage frequency converter in speed control of reciprocating compressor with high frequency is feasible. The actual controllable frequency modulation range of the reciprocating compressor motor with high frequency and high speed is 34Hz to 55Hz, the resonant frequency of compressor and main motor is 51.5Hz, and the effective energy-saving frequency regulation range is 34Hz to 45Hz. The low frequency operation has better energy saving effect, the unit consumption of gas transportation is reduced by about 3%. It can effectively improve the operation efficiency of the compressor and reduce the unit consumption of gas transportation by reasonably controlling the power frequency motor of the reciprocating compressor by the frequency converter.